Analisis Ma‘ani Awzān al-Fi‘l dalam Surah Al-A‘lā: Kajian Makna dan Struktur Bahasa Arab - Muhammad Luthfi Ardiansyah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze ma‘ani awzān al-fi‘l (meaning of verb patterns) in Surah Al-A‘lā using a semantic linguistic approach. The focus of this study is to reveal how the morphological structure of verbs in the Surah forms and strengthens the theological meaning contained in its verses. In Arabic, changes in verb form through wazn or pattern have a major impact on the meaning and function of words. Therefore, each choice of verb form in Surah Al-A‘lā is important to study in depth. This study uses a qualitative approach with a literature study method, relying on classical and modern tafsir literature, as well as Arabic linguistic sources. The results of the study show that the use of various wazn such as فَعَّلَ, أَفْعَلَ, and فَعَلَ in Surah Al-A‘lā not only function as grammatical forms, but also as a means of affirming spiritual and theological meanings. The implications of this study show that the structure of Arabic in the Qur'an contains profound expressive power in conveying divine messages.